WISP1 drives esophageal squamous cell carcinoma progression via modulation of cancer-associated fibroblasts and immune microenvironment - Yi, Zhiqiang; Zhang, Qiqi; Tao, Ting; Liu, Xiaojia; Li, Hui; Li, Xiujuan; Zhang, Zhiqiang (Frontiers in Immunology, 2025)
BackgroundPrevious studies have reported abnormal expression of WNT1-inducible signaling pathway protein 1 (WISP1)/Cellular Communication Network Factor 4 (CCN4) in esophageal squamous cell carcinoma (ESCC). However, its specific significance remains unclear. To date, no in-depth research has been conducted to explore the role and importance of WISP1 in ESCC.MethodsIn this study, we downloaded the expression data of WISP1 (CCN4), Single-Cell RNA Sequencing (scRNA) data, and clinical information from public databases. A combination of bioinformatics analyses and experimental approaches was employed to comprehensively investigate the correlation between WISP1 expression and clinical prognosis, tumor microenvironment (TME), drug resistance, and response to immunotherapy. Additionally, the role of WISP1 in cancer-associated fibroblasts (CAFs) and its underlying mechanisms were explored.ResultsOur findings revealed that WISP1 exhibited differential expression in most analyzed cancers. In ESCC, WISP1 was upregulated and associated with TME characteristics, immune suppression, and drug resistance. Further analysis indicated that ESCC patients with higher WISP1 expression had relatively poorer prognoses. Moreover, it was confirmed that WISP1 is predominantly highly expressed in CAFs. Knockdown of WISP1 in CAFs significantly inhibited their proliferation, migration, and invasion capabilities, as well as markedly reduced the expression of extracellular matrix (ECM) proteins collagen type I alpha 1 chain (COL1A1) and matrix metallopeptidase 14 (MMP14). Notably, co-culture experiments of CAFs with knocked-down WISP1 and ESCC cancer cells demonstrated that the migration and invasion abilities of ESCC cancer cells were also significantly impaired.ConclusionIn summary, WISP1 is intricately involved in the pathogenesis of ESCC, exhibiting multifaceted roles. WISP1 can modulate the activities of CAFs and cancer cells in ESCC, as well as the process of ECM remodeling, thereby influencing the pathological progression of this malignancy. Based on the aforementioned research findings, WISP1 holds promise as a prognostic molecular marker and a potential therapeutic target for ESCC.